A comparison and review of the flow cytometric findings in classic Hodgkin lymphoma, nodular lymphocyte predominant Hodgkin lymphoma, T cell/histiocyte rich large B cell lymphoma, and primary mediastinal large B cell lymphoma. Issue 1 (8th December 2021) - Martig, Daniel S.; Fromm, Jonathan R.
Abstract: The "Hodgkin‐like" lymphomas including classic Hodgkin lymphoma, nodular lymphocyte predominant Hodgkin lymphoma, T cell/histiocyte rich large B cell lymphoma, and primary mediastinal large B cell lymphoma have been shown to be pathobiologically related. With the exception of primary mediastinal large B cell lymphoma, these lymphomas have similar morphologic growth patterns with occasional neoplastic cells within a prominent reactive cell background. Historically, distinguishing these entities was difficult by flow cytometry; however, over the past 15 years, our laboratory has developed antibody‐fluorochrome combinations capable of accurately distinguishing these entities by their immunoprofile. Additionally, an algorithmic approach based on characterization of the background reactive B‐cell and T‐cell populations can aid in narrowing the differential diagnosis. This review summarizes both the morphologic and immunophenotypic features and the current flow cytometric insights of the neoplastic and reactive populations found in this unique subset of lymphomas.